Analysis of the social housing rehabilitation process in Sub-Saharan Africa: The cases of barrio chino and Los Ángeles in Malabo, Equatorial Guinea - SIALE, Josefina MONTE-NGUBA; PADENOU, Guy-Hermann Mawussé; KPOTCHOU, Koffi (Edelweiss Applied Science and Technology, 2025)
Access to decent housing remains a major concern for many households worldwide. This issue is recurrent in cities across sub-Saharan Africa, particularly in Malabo, the administrative capital of Equatorial Guinea, where several social housing projects have been implemented to address the housing shortage. However, these cities are experiencing accelerated deterioration. This deterioration is mainly the result of inappropriate material choices, insufficient maintenance, and the lack of a clear strategy defining the framework for their rehabilitation. Since 2014, sporadic interventions have been implemented to improve the living conditions of residents in social housing estates in Malabo, particularly Los Ángeles and Barrio Chino. However, these actions, often dictated by political considerations and specific events, focus primarily on the physical aspect of buildings, neglecting social, economic, and environmental dimensions. The objective of this research is to analyze the methods used in the rehabilitation of social housing in Malabo. The methodological approach adopted combines both qualitative and quantitative data. A bibliographic review of available empirical resources was conducted to identify the actors involved and evaluate current intervention processes. The results of the study highlight the involvement of a multitude of actors in rehabilitation operations, the ad hoc and summary nature of the work carried out, and the need to adopt an integrated and participatory approach to improve decision-making in future social housing rehabilitation operations in Malabo.